Penilaian Jurnal internasional : The Effect of Manager’s Knowledge of the Availability of Management Accounting Information Systems Based on Activities by Management Way to Control as an Intervening Variable - Widia Astuty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
Penilaian Jurnal internasional : The Effect of Manager’s Knowledge of the Availability of Management Accounting Information Systems Based on Activities by Management Way to Control as an Intervening Variable